Sosialisasi ABDIMAS Universitas Primagraha di Kecamatan Tanara (Sektor Pendidikan dan Sektor Perekonomian Budidaya Udang Vaname) - Aimmatul Khazanah; Akmaliyah Akmaliyah; M Syaiful Millah; Siti Ma’ani; Riki Gana Suyatna (Pusat Riset dan Inovasi Nasional, 2024)
Primagraha University carries out community service activities in several sub-districts in Serang-Banten which aim to improve student development in the social environment. In this case, UPG sent several students to participate in social life in the community. The materials and methods used in this research are descriptive qualitative methods, this type of research basically uses a deductive-inductive approach. The research location